Behavior of a Flat Solid in a Container with Liquid Subject to Large Amplitude Vibration - Victor Kozlov; Olga Vlasova (Shock and Vibration)
We experimentally study the behavior of a flat body in the oscillating container with liquid. The body density is much more than the density of liquid. The body oscillates with large amplitude under the action of inertia forces. It is found that under the vibration the body lifts up and goes to quasi-steady suspended state at some distance from the container bottom. The lift force is measured by a method of dynamic suspension of a body in the gravity field. It is found that the dimensionless repulsion lift force depends on the dimensionless amplitude of the body oscillations; it reduces with the amplitude and is in agreement with the theoretical model in the limit of small amplitude. Qualitatively new regimes of body behavior are found in the supercritical region. With an increase of the vibration intensity, the body gets a stable state in the middle of the container height and then moves on to the container ceiling.